Komunikasi Interpersonal : Interaksi Verbal dan Non Verbal Pemain Game Free Fire di Saree Gampong Suka Damai, Aceh Besar - Sidiq Maulana; Syukri Syamaun; Hanifah Nurdin (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This study examines interpersonal communication in the Free Fire game among children and teenagers in Saree, Gampong Suka Damai, Aceh Besar. The research focuses on verbal and non-verbal interactions that occur during gameplay, both in moments of victory and defeat. The findings reveal that elementary school children tend to communicate in a relaxed manner using simple words and light facial expressions. Meanwhile, junior and senior high school students exhibit more emotional expressions, both verbally using more expressive (sometimes harsh) language and non-verbally, such as hitting the table or throwing their phones when frustrated by a loss.Furthermore, this study highlights that in-game communication not only affects the gaming experience but also influences social interaction patterns in real life. Communication habits developed in the game can extend to daily interactions, potentially affecting players' relationships with their families and peers. Therefore, this research emphasizes the importance of parental supervision and guidance to ensure that children maintain positive communication skills, both in the virtual world and in reality.